2017
DOI: 10.1021/acs.analchem.6b04600
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Disulfide Structure of Murine Meteorin, a Neurotrophic Factor, by LC–MS and Electron Transfer Dissociation-High-Energy Collisional Dissociation Analysis of Proteolytic Fragments

Abstract: Meteorin and Cometin (Meteorin-like) are secreted proteins belonging to a newly discovered growth factor family. Both proteins play important roles in neural development and may have potential as therapeutic targets or agents. Meteorin and Cometin are homologues and contain ten evolutionarily conserved Cys residues across a wide variety of species. However, the status of the Cys residues has remained unknown. Here, we have successfully determined the disulfide structure for murine Meteorin by LC-MS analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…These observations suggest that Metrnα and Metrnβ may have similar functions except that Metrnα is primarily acting in the CNS while Metrnβ may be part of innate immunity. In support of this conclusion, Wen et al have described the disulfide structure of Meteorin α, and observed high conservation of the ten Cys residues between Meteorin α and Meteorin β, suggesting that the disulfide linkages in these proteins are highly conserved (22). A corollary to these observations is that structures and their functions may be similar, although Metrnα will likely exert these effects in the Central Nervous System where it is predominantly expressed while Metrnβ may mediate similar functions in skin, mucosa and inflammatory responses.…”
Section: Discussionmentioning
confidence: 88%
“…These observations suggest that Metrnα and Metrnβ may have similar functions except that Metrnα is primarily acting in the CNS while Metrnβ may be part of innate immunity. In support of this conclusion, Wen et al have described the disulfide structure of Meteorin α, and observed high conservation of the ten Cys residues between Meteorin α and Meteorin β, suggesting that the disulfide linkages in these proteins are highly conserved (22). A corollary to these observations is that structures and their functions may be similar, although Metrnα will likely exert these effects in the Central Nervous System where it is predominantly expressed while Metrnβ may mediate similar functions in skin, mucosa and inflammatory responses.…”
Section: Discussionmentioning
confidence: 88%
“…Other approaches involve more nuanced tactics to study disulfide bonds, including targeted methods to dissociate intrachain disulfide bond containing peptides with ETD based on prior analysis of reduced/alkylated samples and assigning disulfide bond connectivity via extracted ion chromatograms of disulfide bonded peptide pairs that are generated together following ETD reactions. 185 , 186 In all, ETD-based analyses of disulfide bonds have been used in recent studies to investigate neuropeptides, 185 secreted proteins, 182 HIV envelope proteins, 186 and protein storage stability, 187 among other things.…”
Section: Characterizing Post-translational Modifications With Etdmentioning
confidence: 99%
“…Subfatin is also named Metrnl (Meteorin-like), cometin [18], or interleukin 39 (IL-39) [19,20]. The gene of subfatin is located in chromosome 11qE2 in mice and chromosome 17q25.3 in humans, respectively [21].…”
Section: Identification Of Subfatinmentioning
confidence: 99%